A comparison of integrated pest management and conventional practices on insect diversity and economic profitability of cayenne pepper cultivation - MOCHAMMAD SYAMSUL HADI; SHARFINA FARHAH NAZIHA; RIZQIA NUR SALSABELA MULYONO; FAIZ NASHIRUDDIN MUHAMMAD; BINTANG ARYA PRAMANA; ACHMAD FITRIADI TAUFIQURRAHMAN; BINTAR PROBO SUNARTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hadi MS, Naziha SF, Mulyono RNS, Muhammad FN, Pramana BA, Taufiqurrahman AF, Sunarto BP. 2025. A comparison of integrated pest management and conventional practices on insect diversity and economic profitability of cayenne pepper cultivation. Biodiversitas 26: 1519-1525. Cayenne pepper (Capsicum frutescens) cultivation generally relies heavily on insecticide applications. Integrated Pest Management (IPM) offers an effective solution to minimize insecticide use while maintaining crop productivity and sustainability. The objective of this study is to compare insect diversity and economic profitability in cayenne pepper cultivation under IPM and conventional practices. The research was conducted in Sukoharjo Village, Bancar Sub-district, Tuban District, East Java, Indonesia, and in the Plant Pest Laboratory, Universitas Brawijaya, Malang, East Java, from October 2023 to May 2024. Insect sampling was carried out using pan traps and pitfall traps to observe flying and ground-dwelling insects, respectively. Data analysis included diversity indices and economic calculations such as total cost, revenue, profit, break-even point, and benefit-cost (B/C) ratio. The results showed that the IPM system supported a greater number of species (20 species) and a higher total abundance of insects (298 individuals) compared to the conventional system (15 species and 240 individuals). IPM favored the presence of predatory insects such as Paederus sp., Omonadus sp., and Rynocoris sp., whereas conventional practices showed a higher abundance of herbivorous insects such as Myzus persicae and Acrididae sp.. In terms of yield, the IPM system produced 4.74 tons, greater than the 2.55 tons from the conventional system. IPM generated greater revenue and profitability compared to conventional practices. The findings suggest that IPM practices offer dual benefits, enhancing ecological sustainability by increasing predator populations while also improving economic returns for farmers.